Children of time - Tchaikovsky, Adrian, 1972- (London : Pan, an imprint of Pan MacMillan, 2016)
The last remnants of the human race left a dying Earth, desperate to find a new home. Following their ancestors' star maps, they discovered the greatest treasure of a past age--a world terraformed and prepared for human life. But all is not right in this new Eden. The planet is not waiting for them, pristine and unoccupied. New masters have turned it from a refuge into mankind's worst nightmare. Now two civilizations are on a collision course and must fight to survive. As the fate of humanity hangs in the balance, who are the true heirs of this new Earth?
Keywords: Dystopias -- Fiction; Survival -- Fiction; Human-alien encounters -- Fiction; Life on other planets -- Fiction; Planets -- Fiction; End of the world -- Fiction